(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
Microcapsules containing phase change materials (PCM) have been attracting much attention due to its applications in many energy storage fields. However, most PCM microcapsules have relatively low thermostability with an onset decomposition temperature of about 150 ◦C, which to some extent restricts their applications. In this study, high chain ester of dodecanol laurate was first synthesized with raw materials of 1-dodecanol and lauric acid by esterification reaction under catalysis, and then the ester as core material was encapsulated using PMMA by emulsion polymerization. The resultant products, including the ester and the PCM microcapsules, were respectively characterized by using infrared spectroscopy (IR), differential scanning calorimeter (DSC), thermogravimetry (TG), laser particle size analyzer and scanning electron microscope (SEM). The synthesized dodecanol laurate have a high purity according to IR spectrum analysis and suitable phase temperature range of 22-30 ◦C from DSC measurement. In addition, the ester also showed good thermal properties with a latent heat of 206 J/g, small super-cooling degree of 0.5 ◦C and high thermal evaporation temperature of 220 ◦C, which would be very suitable for application in PCM energy storage materials. Using the above ester as core material, the PCM microcapsules were successfully fabricated by emulsification and polymerization processes. The prepared microcapsules showed perfect spherical shape with size about 865 nm and high heat storage performance with a latent energy of 118 J/g. Owing to high evaporation temperature of ester core material itself and further encapsulation, the prepared PCM microcapsules showed higher thermostability. TG results suggested that the microcapsules had a high onset weightless temperature which was over 252 ◦C, it was a significant increment comparing to those PCM microcapsules reported by most literatures. Moreover, thermo-regulating cotton fibers were fabricated by using the above PCM microcapsules. It’s seen that the PCM microcapsules deposited on the fibers uniformly and the fibers had a latent heat of 20.18 J/g.